Rice price shocks and household welfare in Papua New Guinea - Schmidt, Emily; Dorosh, Paul A.; Gilbert, Rachel (International Food Policy Research Institute, 2020)
Rice prices in international markets rose sharply between December 2019 and May 2020, increasing, for example, by 25 percent in Thailand and 30 percent in Vietnam. Given that essentially all of the rice supply for Papua New Guinea (PNG) comes from rice imports, the domestic price of rice in PNG is likely to rise substantially in coming months. Although PNG’s food economy is dominated by domestically produced starchy staples, rice imports have almost doubled from 167,000 tons annually in 2005 to an estimated 300,000 tons in 2020. This note examines rice consumption patterns and international trade trends for PNG to shed light on the potential impacts in rural and urban PNG of disruptions to rice imports. Our model simulations indicate that a 30 percent rise in the world price of rice would be expected to decrease the rice consumption of poor households by 17.3 percent. Under this scenario, consumers in poor households, which are those in the bottom 40 percent of the household expenditure distribution in PNG, would suffer a net welfare loss of USD 23.0 million, equivalent to a 1.6 percent decrease in a per capita daily income of one US dollar.